2022
DOI: 10.14715/cmb/2021.67.4.29
|View full text |Cite
|
Sign up to set email alerts
|

Study of ultrasound-guided ropivacaine combined with butorphanol continuous paravertebral block to prevent pain syndrome by evaluating ccl2 gene expression after radical mastectomy

Abstract: This study aimed to investigate the clinical effect of ultrasound-guided ropivacaine combined with butorphanol continuous paravertebral block in preventing postoperative pain syndrome of breast cancer. For this purpose, 100 women treated for breast cancer from April 2018 to July 2019 were enrolled as research objects. Surgical procedures included local sentinel lymph node biopsy, mastectomy, sentinel lymph node biopsy for mastectomy, modified radical mastectomy, and implantation. The selected patients were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Our data showed that the probability of vomiting after surgery in the control group was higher than that in the study group; this was because the hemodynamic status of patients in the study group was relatively stable and the intake of opioid doses was reduced. Hence, the overall situation of patients tended to be good following surgery [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the probability of vomiting after surgery in the control group was higher than that in the study group; this was because the hemodynamic status of patients in the study group was relatively stable and the intake of opioid doses was reduced. Hence, the overall situation of patients tended to be good following surgery [31,32].…”
Section: Discussionmentioning
confidence: 99%